RRI Purwokerto Rural Broadcasts in 1970-1990s - Prabasanti, Mustika Ratna (Universitas Negeri Yogyakarta, 2024)
AbstractThis research explores Rural Broadcasting of RRI Purwokerto in the 1970-1990s. Rural Broadcasting is a program to support the achievement of the national economic development program, particularly in the food security sector. The objective of this research is to reveal (1) the role of RRI Purwokerto as a broadcasting institution in implementing rural broadcasting programs, (2) observe the interest of the community in the Banyumas region and its surroundings towards rural broadcasting programs, and (3) explore the driving factors for success in implementing Rural Broadcasting of RRI Purwokerto, making it a pivotal program. The results of this research are as follows: (1) The implementation of Rural Broadcasting by RRI Purwokerto began on October 1, 1968, despite various limitations. Together with RRI Yogyakarta, RRI Purwokerto succeeded in pioneering the implementation of rural broadcasting in Indonesia. (2) The community's high interest is evident in its response with the formation of